2021
DOI: 10.21203/rs.3.rs-236927/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of MITE-derived microRNAs and their targets in bread wheat

Abstract: Plant microRNAs (miRNAs) are a class of small non-coding RNAs that are 20–24 nucleotides length and can repress gene expression at post-transcriptional levels by target degradation or translational repression. There is increasing evidence that some microRNAs can be derived from a group of non-autonomous class II transposable elements called Miniature Inverted-repeat Transposable Elements (MITEs) in plants. We used public small RNA, degradome libraries and the common wheat (Triticum aestivum) genome to screen m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In wheat, TamiR113, which has dynamic expression under adverse conditions, was found to be derived from a MITE (Yu et al, 2014). Recently, a genome‐wide study revealed that among a total of 270 miRNAs, 38 miRNAs, including 10 24‐nt miRNAs, are derived from MITEs in wheat (Crescente et al, 2022). Here we found that more than half of lmiRNAs are derived from MITEs in rice seedlings, further supporting that MITEs are an important origin of small RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, TamiR113, which has dynamic expression under adverse conditions, was found to be derived from a MITE (Yu et al, 2014). Recently, a genome‐wide study revealed that among a total of 270 miRNAs, 38 miRNAs, including 10 24‐nt miRNAs, are derived from MITEs in wheat (Crescente et al, 2022). Here we found that more than half of lmiRNAs are derived from MITEs in rice seedlings, further supporting that MITEs are an important origin of small RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TEs contain regulatory sequences such as promoters, transcription factors binding sits, and target sites for post-transcriptional degradation, which might affect adjacent gene expression or even modulate gene expression through complex transcriptional regulatory networks ( Bourque et al., 2018 ; Dubin et al., 2018 ; Qiu and Köhler, 2020 ; Zhang et al., 2021 ). Additionally, the insertion of TE into a gene body might result in the creation of new isoforms through exonization, truncation, alternative splicing, or even by the domestication of TE-derived coding sequences into host genes, potentially altering the gene function ( Keidar et al., 2018 ; Poretti et al., 2019 ; Crescente et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observation led Ramírez-González et al., 2018 to suggest a possible role for TEs in gene regulation as cis-regulatory elements or through other epigenetic mechanisms in a tissue-specific manner. Moreover, recent studies showed that TEs, specifically MITEs (Miniature Inverted repeat TEs), which are prevalent in the vicinity of wheat genes, might act as miRNAs precursors in wheat and thus can potentially shape regulatory gene networks ( Poretti et al., 2019 ; Crescente et al., 2022 ). While the effect of TE insertions into promoter regions in wheat has been well-investigated, very little is known about the possible effect of TE insertions within gene bodies ( Li et al., 2014 ; Xi et al., 2016 ; Keidar et al., 2018 ; Keidar-Friedman et al., 2018 ; Domb et al., 2019 ; Jiang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One key feature of MITEs is that their transcripts can fold into hairpin-shaped dsRNAs due to the extensive sequence complementarity between IR arms. These dsRNA secondary structures are recognized and processed by DCL3 to produce 24-nt siRNAs that trigger DNA methylation without the need for RNAPIV/RDR2 activity (Ariel and Manavella, 2021;Crescente et al, 2022;Cuerda-Gil and Slotkin, 2016;Gagliardi et al, 2019;Sasaki et al, 2014). Thus, transcripts of these MITEs can be initiated from promoters of adjacent genes, triggering their RNA Polymerase II (RNAPII)dependent DNA methylation.…”
Section: Introductionmentioning
confidence: 99%